Exposure to Triclosan and Bisphenol Analogues B, F, P, S and Z in Repeated Duplicate-Diet Solid Food Samples of Adults - Marsha K. Morgan; Matthew S. Clifton (Toxics, 2021)
Triclosan (TCS) and bisphenol analogues are used in a variety of consumer goods. Few data exist on the temporal exposures of adults to these phenolic compounds in their everyday diets. The objectives were to determine the levels of TCS and five bisphenol analogues (BPB, BPF, BPP, BPS, and BPZ) in duplicate-diet solid food (DDSF) samples of adults and to estimate maximum dietary exposures and intake doses per phenol. Fifty adults collected 776 DDSF samples over a six-week monitoring period in North Carolina in 2009–2011. The levels of the target phenols were concurrently quantified in the DDSF samples using gas chromatography/mass spectrometry. TCS (59%), BPS (32%), and BPZ (28%) were most often detected in the samples. BPB, BPF, and BPP were all detected in <16% of the samples. In addition, 82% of the total samples contained at least one target phenol. The highest measured concentration of 394 ng/g occurred for TCS in the food samples. The adults’ maximum 24-h dietary intake doses per phenol ranged from 17.5 ng/kg/day (BPB) to 1600 ng/kg/day (TCS). An oral reference dose (300,000 ng/kg/day) is currently available for only TCS, and the adult’s maximum dietary intake dose was well below a level of concern.